(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | Marshall McLuhan’s ideas have been foundational in shaping understandings about the role of media and mediation in landscape, identity, and nationhood. At the same time, his theories remain tethered to a liberal humanist schematic of citizenship and technological modernity, which advances—implicitly or not—colonial constructions of the land as terra nullius, and thus severely limits or frustrates attempts to enlist them in anti-colonial analyses. In response, this paper places McLuhan into dialogue with Cree artist and scholar Cheryl L’Hirondelle, arguing that such a move can begin to disrupt the settler underpinnings in McLuhan’s ideas, and also broaden the potential for these ideas to be applied within contemporary queries into decolonial citizenships on Turtle Island. Our paper focuses on L’Hirondelle’s nikamon ohci askiy (songs because of the land). An interactive digital platform framed through Cree cosmology, nikamon ohci askiy is a multilayered work that explores technological mediations of nation, land, and Indigenous citizenship. Similar to other Indigenous theories of new media, this work challenges the view of land as barren/hostile, in particular by emphasizing land-based animate relationships. Ultimately, this paper argues that the new media ecologies proffered through L’Hirondelle’s work contest settler liberal citizenship, and reorients understandings of “networks” and “the digital” as crucially grounded in Indigenous notions of reciprocality and relationality Résumé | Les idées de Marshall McLuhan ont été fondamentales dans l’élaboration des compréhensions sur le rôle des médias et de la médiation dans le paysage, l’identité, et l’idée de la nation. En même temps, ses théories restent attachées à schéma humaniste libéral de la citoyenneté et de la modernité technologique qui avance, implicitement ou non, les constructions coloniales de la terre comme terra nullius, et limite ainsi ou freine sévèrement les tentatives de les enrôler dans des analyses anticoloniales. En réponse, cet article établit un dialogue entre McLuhan et Cheryl L’Hirondelle, artiste et universitaire crie, soutenant qu’un tel mouvement peut commencer à perturber les fondements qu’ont les colons des idées de McLuhan, et également élargir la possibilité que ces idées soient appliquées dans les requêtes contemporaines de décolonisation des citoyennetés sur l’Île de la Tortue. Notre article se concentre sur les nikamon ohci askiy de L’Hirondelle (chansons à cause de la terre). Plateforme numérique interactive encadrée par la cosmologie crie, nikamon ohci askiy est un travail complexe qui explore les médiations technologiques de la nation, de la terre, et de la citoyenneté autochtone. Comme d’autres théories autochtones sur les nouveaux médias, ce travail remet en question la vision de la terre comme stérile/hostile, en particulier en mettant l’accent sur les relations animées terrestres. En fin de compte, cet article soutient que les écologies des nouveaux médias véhiculées par le travail de L’Hirondelle contestent la citoyenneté libérale des colons et réorientent la compréhension des « réseaux » et du « numérique » comme fondamentalement ancrée dans les notions autochtones de réciprocité et de relationnalité.